Biological Research in Aquatic Science - Bozkurt, Yusuf (IntechOpen, 2019)
Biological research has a wide range of applications in aquatic science, which explores aquatic organisms' morphological and physiological characteristics, their behavior and interactions, and their surrounding environment. Organized into five sections and written by experts in their respective fields, Biological Research in Aquatic Sciences covers topics including cryobiology, spermatology, climate change, migration of aquatic species, and plankton in aquatic ecosystems. This book will help researchers and interested readers better understand current trends in biological research regarding aquatic science.